Antidiabetic Test of Ethanolic Extract of Ant Nest Plants (Myrmecodia sp.) Against the -Glucosidase Enzyme In Vitro - Daniel, Daniel; Isa, Muhammad; Hasan, Muhammad; Sari, Wahyu Eka; Rosmaidar, Rosmaidar; Aisyah, Siti; Athaillah, Farida; Frengki, Frengki (Universitas Syiah Kuala, 2024)
The use of plants, one of the biological sources, as an alternative medicine for degenerative diseases is increasingly being studied. Usually, the biological effects of these plants come from the secondary metabolite components contained therein. Ant nest is one of them which is reported to contain compounds belonging to the class of flavonoids, tannins, and polyphenols. This research was conducted in vitro by observing the antidiabetic potential of the ethanolic extract of ant nests against the -glucosidase enzyme following the modified